2020
DOI: 10.1371/journal.pone.0227602
|View full text |Cite
|
Sign up to set email alerts
|

Disease-related and age-related changes of anterior chamber angle structures in patients with primary congenital glaucoma: An in vivo high-frequency ultrasound biomicroscopy-based study

Abstract: Objectives To provide in vivo measurements of anterior chamber angle structures and their relationship with age as evaluated by high-frequency ultrasound biomicroscopy (UBM) in patients with primary congenital glaucoma (PCG) Methods High-frequency UBM was done for 51 PCG eyes from 40 patients (aged from 3 to 96 months) and 11 unaffected contralateral eyes. Parameters, including the proportion of observable abnormal tissue membrane and Schlemm's canal, the largest cross-sectional area (CSA) of Schlemm's canal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…A dysplastic ciliary body with a longer ciliary process has also been seen in primary congenital glaucoma (PCG), however the longer ciliary process may have been caused by the stretched globe. 27 Although a short history of glaucoma and normal eyeball size ruled out a diagnosis of PCG in this case, the similar changes in the ciliary process further support that a dysplastic ciliary might be easily stretched out.…”
Section: Discussionsupporting
confidence: 50%
“…A dysplastic ciliary body with a longer ciliary process has also been seen in primary congenital glaucoma (PCG), however the longer ciliary process may have been caused by the stretched globe. 27 Although a short history of glaucoma and normal eyeball size ruled out a diagnosis of PCG in this case, the similar changes in the ciliary process further support that a dysplastic ciliary might be easily stretched out.…”
Section: Discussionsupporting
confidence: 50%
“…Trabecular iris angle (TIA): constructed of a line along the inner surface of the cornea and a line along on the opposite anterior iris surface and measured in degrees (Gupta et al 2007;Hussein et al 2014) root and the most probable location of the scleral spur, measured 500 lm (Shi et al 2020) or 2 mm (Hussein et al 2014 andGupta et al 2007) from the iris root; 4. Ciliary process length (CPL): measured from the point of the most anterior tip of the ciliary body to the beginning of the zonules (Shi et al 2020end Gupta et al 2007); 5. Corneal thickness (CT): measured from the scleral spur to the outer surface of the corneal limbus (Shi et al 2020) or from the centre inner surface of the corneal endothelium to the outer epithelial surface (Hussein et al 2014); 6.…”
Section: Methodsmentioning
confidence: 99%
“…3 The UBM is an invaluable diagnostic and prognostic tool in evaluating anterior segment pathology including aniridia, iridolenticular adhesions, anterior chamber angle structures, and limbal dermoids. [54][55][56][57] In their series, Nischal and colleagues reported that UBM diagnosis agreed 100% with the histologic diagnosis, while 5/13 (38%) of cases were clinically misdiagnosed as sclerocornea (2), keratectasia (1), and congenital glaucoma (2). Respectively, Peter anomaly (first 3 cases) and congenital corneal dystrophy (last 2 cases) were diagnosed using UBM and confirmed histologically.…”
Section: Ubmmentioning
confidence: 97%